Trends in Secondary School Practices Related to Violence Prevention, 2012‐2018. (17th May 2022) - Adhia, Avanti; Schleimer, Julia P.; Mazza, James
ABSTRACT: BACKGROUND: Schools are important venues for addressing interpersonal violence among youth. However, it is unclear to what extent school violence prevention practices have been implemented across states and over time. This study examined trends in the percentage of US secondary schools that engaged in practices related to violence prevention (eg, bullying, fighting, dating violence) across 33 states. METHODS: With representative data from 4 waves (2012‐2018) of School Health Profiles, we used logistic regression to examine change over time of 5 practices related to violence prevention in school‐based settings: professional development for health education teachers (received and would like to receive); increasing student knowledge; and teaching healthy and respectful relationships in grades 6‐8 and grades 9‐12. RESULTS: Two practices had rates of adoption >90% across years (tried to increase student knowledge on violence prevention and taught healthy and respectful relationship in grades 9‐12). Adoption of professional development on violence prevention for health education teachers was lowest (53%‐61% across years). For all practices, most states experienced no change in the percentage of schools implementing violence prevention practices from 2012 to 2018. CONCLUSION: Education about healthy relationships in middle school and professional development on violence prevention for health education teachers are needed.